The Education on the Importance of Protecting from the Dangers of Chickenpox Through Audiovisual Learning Media: Edukasi Pentingnya Menjaga Diri dari Bahaya Cacar Air Melalui Media Pembelajaran Audiovisual - Esme Anggeriyane; Suci Fitri Rahayu; Dea Salamiah; Doni Bilman Murizki; Mimin Hafizatul Maulida (Lembaga Riset Ilmiah, 2022)
Chickenpox or the disease caused by the Varicella Virus is no stranger to society and the world. This disease is an infectious disease that is very common in children and adults are no exception. Chickenpox attacks children aged 5-9 years. Chickenpox is transmitted very quickly through fluids from the body such as sneezing or coughing from one individual to another, so it is possible that the person will be infected. The purpose of this education was to increase knowledge and awareness of healthy students about the dangers of chickenpox through Audio Visual Learning Media for School Children. The activity done in a day on June 17, 2022, with a duration of 1 hour from 09.00–10.00 a.m. Location of activity at Madrasah Ibtidaiyah Muhammadiyah 3 “Al – Furqan” Banjarmasin for 2D grade students. Evaluation of the implementation of these activities was to determine the extent of students' knowledge about chickenpox disease with achievements that can be seen from changes in scores from before and after the test. Most of the students experienced a change in knowledge about the education that had been given. The percentage of students' knowledge before being given education has an average value of 83.3% and after being given education it is 88.9% so that the results of the two aspects have changed around 5.6%.